2022
DOI: 10.1016/j.cell.2021.12.017
|View full text |Cite
|
Sign up to set email alerts
|

RTN4/NoGo-receptor binding to BAI adhesion-GPCRs regulates neuronal development

Abstract: In the introduction of the original article, we neglected to cite a previous systematic receptor-ligand interaction screen that identified, among others, binding of BAI1 TSR domains to RTN4Rs and lack of binding of BAI2 (Chong et al., 2018

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Such myelin-associated inhibitors that are presented on the surface of oligodendrocytes include, NogoA 68 and Omgp 69 . BAIs also were recently discovered to inhibit axon growth by live oligodendrocytes co-cultured with neurons 27 . Thus, we investigated whether these inhibitors of axon growth are expressed by post-injury-born immature oligodendrocytes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such myelin-associated inhibitors that are presented on the surface of oligodendrocytes include, NogoA 68 and Omgp 69 . BAIs also were recently discovered to inhibit axon growth by live oligodendrocytes co-cultured with neurons 27 . Thus, we investigated whether these inhibitors of axon growth are expressed by post-injury-born immature oligodendrocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is possible that primarily the premature de novo myelination, rather than the pre-existing myelin and its debris, is what stalls experimental regeneration even after axons have bypassed the inhibitory glial scar. Indeed, conditional deletion in oligodendrocytes of the neurological diseases-associated brain-specific angiogenesis inhibitors (BAIs; which bind to the axon growth-inhibitory NogoA reticulon-4 receptor; Rtn4R), was recently shown to rescue axonal growth of co-cultured neurons 27 , further supporting our hypothesis that live oligodendrocytes, and not only their debris after injury, could inhibit axon regeneration. To test our hypothesis, we used single cell RNA-seq (scRNA-seq) to analyze the effects of ONC on optic nerve oligodendrocytes, and a cuprizone-induced chronic demyelination (that injures oligodendrocytes to model multiple sclerosis) during traumatic optic neuropathy (modeled by ONC), which acutely and irreversibly disrupts the neuronal axons while modifying the extra-axonal tissue environment 2 .…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Recent data suggests that O -fucosylation on TSRs is not only important for folding and secretion but has functions in the extracellular environment as well. A recent study showed that an O -fucose on TSR3 of brain-specific angiogenesis inhibitor 1 (BAI1) is in direct contact with its ligand, reticulon-4 receptor (RTN4R) ( 42 ). BAI–RTN4R interactions control dendritic arborization, axon elongation, and synapse formation.…”
Section: Discussionmentioning
confidence: 99%
“…With 33 members in the human genome, adhesion G protein-coupled receptors (aGPCRs) represent the second-largest subfamily of GPCRs. Genetic studies have identified critical roles for aGPCRs in development, immunity, and neurobiology 1 7 linking them to numerous diseases including neurodevelopmental disorders, deafness, male infertility, schizophrenia, immune disorders, and cancers 2 , 8 15 . While aGPCRs are crucial surface receptors involved in numerous physiological processes 16 , establishing an understanding of their mechanisms of action at the molecular level remains an ongoing challenge, as has been the development of tools to more effectively study them and to modulate their functions.…”
Section: Introductionmentioning
confidence: 99%